2020
DOI: 10.1371/journal.pone.0225783
|View full text |Cite
|
Sign up to set email alerts
|

The impact of end-demand legislation on sex workers’ access to health and sex worker-led services: A community-based prospective cohort study in Canada

Abstract: Background Following a global wave of end-demand criminalization of sex work, the Protection of Communities and Exploited Persons Act (PCEPA) was implemented in Canada, which has implications for the health and safety of sex workers. This study aimed to evaluate the impact of the PCEPA on sex workers' access to health, violence, and sex worker-led services. Methods Longitudinal data were drawn from a community-based cohort of~900 cis and trans women sex workers in Vancouver, Canada. Multivariable logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…SWs and third parties (eg, managers) often avoid carrying or storing sufficient condoms due to fear that this will be used as evidence of criminalised activities;27 31 given the continued criminalisation of third-party activities under ‘end-demand’, such concerns are likely to persist 22. Additionally, SWs may avoid interacting with health or outreach services due to stigma and fear of legal ramifications 20 23 27 31. Decriminalisation would enable SWs and workplaces to carry, store and use HIV/STI prevention supplies without fear of criminalisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SWs and third parties (eg, managers) often avoid carrying or storing sufficient condoms due to fear that this will be used as evidence of criminalised activities;27 31 given the continued criminalisation of third-party activities under ‘end-demand’, such concerns are likely to persist 22. Additionally, SWs may avoid interacting with health or outreach services due to stigma and fear of legal ramifications 20 23 27 31. Decriminalisation would enable SWs and workplaces to carry, store and use HIV/STI prevention supplies without fear of criminalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Because this legislation was introduced in 2014, we excluded this year from analysis due to variation in how the laws may have been enforced, as well as the first 3 months of 2015 to account for measures referring to the previous 6 months. This measure was selected since the new laws primarily target clients and third parties rather than SWs, alongside evidence that SWs’ health outcomes and access are often greatly shaped by fear/anxiety related to SW laws (eg, avoidance of accessing services or working in certain venues/areas due to fear of criminalisation) 23 26 27. Questions on criminalisation and policing included experiences of police harassment without arrest (eg, threatened with arrest/detainment/fine, verbally harassed, physically assaulted, propositioned to exchange sex) and police arrest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was initially implemented in an effort to eliminate the sex industry by criminalizing buyers and shielding sex workers from criminal liability. Ultimately, this approach has failed to reduce the number of individuals entering the industry and has exacerbated existing stigma and safety concerns (Giametta, Le Bail and Leicester, 2018;Argento et al, 2020). Indeed, recent research into the impacts of Canada's end-demand model suggests that it is ineffective; changes are required to improve the working conditions of Canadian sex workers (Bruckert and Hannem, 2013;Krüsi, Kerr et al, 2016;Argento et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research evaluating the impact of Canada's new end-demand laws (Protection of Communities and Exploited Persons Act; PCEPA) in Vancouver found that sex workers had significantly reduced access to health and community-led services as a result of the implementation of end-demand criminalisation [50]. Qualitative findings from Sweden and Canada underscore that criminalising clients reproduces the harms of full criminalisation models [51,52].…”
Section: The Impacts Of Criminalisationmentioning
confidence: 99%